Capacidad de Aspergillus niger y Aspergillus flavus aislados de efluente aurífero de adsorber ión plumboso en soluciones acuosas - ENRIQUEZ QUIROZ, Richard Diosdado (2019)
Aspergillus species from a gold effluent from the Huamachuco district located in the Sánchez Carrión province, La Libertad region were isolated and the ability to absorb plumbose ion (Pb+2) from isolated and identified fungi was evaluated._x000D_ The isolation was carried out in Potato Dextrose Agar at pH 4 and the identification was carried out by observing microscopic characteristics with the help of the Piontelli taxonomic key. A suspension was prepared from the pure cultures, obtaining a final concentration of 1x106 conidia / mL in 500 mL of Potato Dextrose Broth, which was placed in an orbital shaker for 5 days. The biomass was filtered, treated with 0.1 N HNO3, dried at 60 °C, pulverized and screened in a range of 720 um to 180 um._x000D_ Subsequently, one gram of biomass was placed in aqueous solution with an initial concentration of 98.33 ppm and 98.44 ppm of Pb+2, taking 20 mL samples at the beginning and at the end of the evaluation. The samples were analyzed by atomic absorption spectrometry to determine the amount of Pb+2 adsorbed._x000D_ Aspergillus niger and Aspergillus flavus were isolated which have an adsorption capacity of 72.89 ppm and 18.37 ppm of Pb+2 respectively.